«Dante Alegieri poeta fiorentino» (vero o presunto) nel primo testo a stampa a noi giunto pubblicato in Liguria (1474) (Carte Romanze, 2022)
The essay analyses the presence of the figure of Dante and verses from the Commedia in a booklet bearing the title La Raxone de la Pasca e de la luna e le feste, which, to the best of our knowledge, is the first text printed in Liguria, being ascribable to 1474, i.e. - note - only two years after the princeps of the poem.
Keywords: Dante; Indirect tradition; printed tradition; Liguria